Density Functional Theory Study of the Hydrogen Bonding Interaction of Complexes of Dimethyl Sulfoxide with Water - Liu, Tao; Yu, Zhang-Yu (Asian Journal of Chemistry, 2010)
The hydrogen bonding of complexes formed between dimethyl sulfoxide and water molecule have been investigated in the present study using density functional theory and second-order moller-plesset perturbation (MP2) method at varied basis set levels from 6-31g to 6-311++g (2d,2p). Two reasonable geometries on the potential energy hypersurface of DMSO and H2O system are considered. The solution phase studies are also carried out using the Onsager reaction field model with a range of dielectric constants at the B3LYP/6-311++g (d,p) level.